Research on variable impedance control of SEA-driven upper limb rehabilitation robot based on singular perturbation method - Bingshan Hu; Hao Ren; Zhou Zhou; Fengchen Liu; Hongliu Yu (International Journal of Advanced Robotic Systems)
This paper proposes a variable impedance control strategy based on the singular perturbation method to address the challenges of achieving accurate impedance characteristics and mitigating stability degradation in two-degree-of-freedom planar SEA-driven robots. By decomposing the system into fast and slow subsystems, we control them separately to improve tracking performance, disturbance rejection, and impedance control. A MATLAB/Simulink model was developed for simulation and compared with a traditional PD controller. The results show that the proposed controller outperforms the PD controller, maintaining position errors under 10% and impedance errors under 30% of those seen with the PD controller under external force input. Additionally, experimental validation confirmed the controller's ability to optimally adjust robot stiffness in response to changes in the user's limb-end stiffness, supporting the assist-as-needed strategy.